The influence of perceived macro environment on the competitiveness of internationalized medium-sized and large enterprises - Miklós Stocker; Ádám Erdélyi (Administrative Sciences, 2024)
Firm competitiveness is a crucial trait of companies which managers strive to improve, and even policy makers focus on it regarding economic development. As companies are embedded into different layers of the environment, this study aims to identify the influence of top managerial perception about the external environment on the firm-level competitiveness of medium-sized and large internationalized companies. The investigation is based on the 6th round of the Competitiveness Survey conducted in Hungary between October 2018 and July 2019 from which n = 107 medium sized or large companies qualified for this study. The institution-based view from the strategic management literature was chosen to differentiate the variables in the macroeconomic environment of the firm while the FCI index was used to measure firm-level competitiveness. After conducting factor and regression analyses, the results show that the perceived macro environment is positively related to the competitiveness of internationalized medium-sized and large companies. Managerial perceptions on civil service and education had the strongest significant positive association with firmlevel competitiveness, whereas perceptions on social and ecological expectations had a significant positive association with the Adaptivity of the firm. This study contributes to the existing body of literature by demonstrating that, even within contentious institutional contexts, the perceptions of internationalized medium and large companies' top managers regarding education, civil service, and social and ecological expectations have a discernible influence on the competitiveness of these companies.
Keywords: 350; institution-based view; macroeconomic environment; firm-level competitiveness; medium-sized and large enterprises; internationalization; strategic management